Analisa Rasio Laporan Keuangan Untuk Menilai Kinerja Perusahaan PT Ace Hardware Indonesia Tbk - Denny Erica; Hoiriah Hoiriah; Mulyadi Mulyadi (LPPM Universitas Bina Sarana Informatika, 2021)
Abstract - PT Ace Hardware Indonesia Tbk was founded in 1995 and is engaged in household and lifestyle equipment business, with 208 outlets spread across 49 cities and 27 provinces. The company has been listed as an issuer on the Indonesia Stock Exchange since 2007 with the exchange code